Family firms and innovation from founder to successor - Francesca Maria Cesaroni; Gail Denisse Chamochumbi Diaz; Annalisa Sentuti (Administrative Sciences, 2021)
Several empirical investigations indicate that family firms are more innovative under the founding generation's leadership and become less innovative in later stages, while others state the opposite. Within this debate, limited attention has been devoted to understanding how intra-family succession might be an opportunity to maintain or improve family firms' innovativeness. This paper aims to explore how family firms' innovativeness may evolve from the first to the second generation and understand which conditions may favour or hamper this change. A qualitative approach based on a multiple case study was adopted, conducting seven face-to-face semi-structured interviews with founders and successors that formed the basis of four case studies. The results reveal four different dynamics that characterise how a first-generation family firm's innovation capacities are or are not passed on to the second generation: decline, transformation, consolidation and preservation. Findings also show that these dynamics depend on the founders and successors' approaches towards innovation. To better depict differences between them, we propose a typology of founders (lone innovator, collaborative innovator and orchestrator innovator) and successors (prodigal son, game changer, talent scout, faithful disciple) and explain how they influence the evolution of innovation from the founder generation to the next.
Keywords: 350; family firm; first and second generations; founder; innovativeness; intra-family succession; Italian family firms; multiple case study; successor; typology